Posttraumatic stress disorder symptoms, relationship quality, and risky alcohol use among trauma-exposed students - Paltell, Katherine C. (Addict Behav, 2019)
Individuals with posttraumatic stress disorder (PTSD) are at increased risk for alcohol use disorder (AUD), in part due to the use of alcohol as a coping strategy. High quality romantic relationships can buffer individuals against risk for psychopathology; however, no studies have evaluated romantic relationship quality in risk for PTSD-AUD in non-clinical samples. The current study examined the main and interactive effects of PTSD symptoms and romantic relationship quality on alcohol consumption (i.e., past 30-day alcohol use quantity, frequency, and binge frequency) and alcohol-related consequences in a sample of 101 college students (78.2% women) with a history of interpersonal trauma (i.e., physical/sexual assault, excluding intimate partner violence) who reported being in a romantic relationship. Relationship quality significantly moderated the association between PTSD symptom severity and alcohol use quantity (B = −0.972, p = .016) and alcohol-related consequences (B = −0.973, p = .009), such that greater PTSD symptoms were associated with greater alcohol use quantity and consequences among those low, but not high, in relationship quality. The interaction between PTSD symptom severity and relationship quality in relation to binge drinking was marginally significant (B = −0.762, p = .063), and relationship quality did not significantly moderate the association between PTSD symptom severity and alcohol use frequency. The main effect of PTSD symptom severity was significantly associated with alcohol-related consequences, but no other alcohol outcomes; the main effect of relationship quality was not associated with alcohol use outcomes or consequences. High quality romantic relationships may serve as a buffer for young adults at risk for alcohol problems.